The Issue of Racial Microagression in Indian-American Children’s Novel: American as Paneer Pie by Supriya Kelkar - Ariza Purnawati (Jurnal Bahasa, Sastra, dan Studi Amerika, 2023)
This research attempts to highlight the issue of microaggressions that occurs in American ethnic minority groups, particularly among Indian-American children featured in the children's novel American as Paneer Pie. Published in 2020, this novel is written by an Indian-American writer named Supriya Kelkar. American as Paneer Pie tells about the story of Lekha, an Indian-American girl who faces racial microaggressions at school. This research identifies the acts of racial microaggressions that occur to the character Lekha in the novel American as Paneer Pie. As a literary analysis, this research uses intrinsic approaches by Pickering and Hoeper as the intrinsic analysis and the theory of microaggressions by DeraldWing Sue as the extrinsic analysis to reveal the problems. The research findings indicate that there are found some acts of racial microaggressions faced by Lekha as an Indian American girl such as mispronouncing her Indian name, stereotyping her Indian physical appearance and lifestyle, and marginalizing her as the minority in the class. These racial microaggressions finally influence her life to change herself to voice her right as the American.